INVESTIGATION OF NEW MAGNETIC NANOMATERIALS WITH COHERENT MAGNETODYNAMIC EFFECTS - Demenev, A.G.; Belozerova, T.S.; Ponomarev, R.S.; Salgaeva, U.O.; Sosunov, A.V.; Kharebov, P.V.; Henner, V.K. (Perm Federal Research Centre Journal, 2017)
Experimental research, aimed at obtaining and studying the magnetic properties of three- dimensional graphene nanoshells and bimetallic nanostructures, has been performed. A reliable and inexpensive method of obtaining graphene nanoshells has been developed. An abrupt change in the direction of the magnetization vector has been detected in the studied nanocomposite samples with bimetallic particles of Co-Ag upon application of an alternating magnetic field. It is shown that magnetization reversal takes place in a fairly narrow range of values of the magnetizing field. Theoretical research was focused on the development of the processes of collective magnetic relaxation occurring in different types of nanostructures. We studied magnetodynamics in nanostructures successfully using computer simulation on supercomputers. The estimates of the parallel acceleration and parallelization efficiency of Magnetodynamics-F code on multi-core and many-core processors were obtained.